Unstash the Cash! : Corporate Governance Reform in Japan - Aoyagi, Chie (IMF Working Papers; Working Paper ;, 2014)
Japan's high corporate savings might be holding back growth. We focus on the causes and consequences of the current corporate behavior and suggest options for reform. In particular, Japan's weak corporate governance-as measured by available indexes-might be contributing to high cash holdings. Our empirical analysis on a panel of Japanese firms confirms that improving corporate governance would help unlock corporate savings. The main policy implication of our analysis is that comprehensive corporate governance reform should be a key component of Japan's growth strategy.